Failure Sustainable Wireless Backhaul - Chai, Pey San Nancy; Chung, Kah-seng; Chan, King-Sun (APCC2009 Technical Program Committee, 2009)
Backhaul network plays a significant role to interconnect access points and further connect them to gateway nodes. A failure sustainable wireless backhaul topology is proposed to ensure undisrupted telecommunication services even in the presence of occasional node or link failures. Furthermore, a new control message, called reverse notification, is proposed to improve the performance of coordinated distributed scheduling in the ladder topology. Computer simulation results show that the reverse notification scheme has improved the network throughput and reduced the packet transmission delay.